The Role of Green Infrastructure Solutions in Urban Flood Risk Management - Soz, Salman Anees (World Bank, Washington, DC, 2016)
This Knowledge Note explores the role of green infrastructure solutions in urban flood risk management. Green infrastructure solutions represent an approach that focuses on using natural processes for managing wet weather impacts while delivering environmental, social, and economic benefits. Green infrastructure solutions, such as wetlands, bioshields, buffer zones, green roofing, street side swales, porous pavements, wetlands, mangroves, etc., are part of an integrated approach to flood risk management which relies on a balance of structural and non-structural measures.